NEW DATA ABOUT AGE AND GEODYNAMIC NATURE OF HAMSARA TERRANE - S. I. Shkolnik; L. Z. Reznitsky; E. F. Letnikova; A. I. Proshenkin (Геодинамика и тектонофизика, 2017)
On the basis of isotopic-geochemical studies and analysis of geological evidences heterogeneity of Hamsara terrane has been determined. Formation of stationed metamorphosed layers underlying the Hamsara formation occurred not earlier than 630 Ma, probably in the oceanic island arc system. Acidic effusive rocks of Hamsara formation were formed in intraplate condition in the range of 462–464 Ma. Sediments of Hamsara formation couldn’t be the part of island arc system and belong to completely other period of geological region development. This is the time of completion of accretion-collision events in the northern part of Altai-Sayan fragment of CAFB adjacent to the Siberian platform.